INDEPENDENCE AND PERFORMANCE OF THE DEGREE PRIMARY SCHOOL TEACHER (Study of Social Reality Independence and Teacher Performance Open University Graduates in Bojonegoro Region) - *, Mujadi (IJRDO- Journal of Educational Research, 2017)
Whether or not the quality of education is very dependent on who is running theeducation itself. The level of student achievement is also highly dependent on the quality of theteachers who carry out the learning to the learners. Education in Indonesia has made a newparadigm in addressing the low quality of education and achievements of learners throughincreasing academic qualifications for teachers who teach in primary school to high-schoollevel. Improvement of qualification of teachers specifically focused on the most elementaryschool teachers from the School of Teacher Education qualification (SPG) and the Diploma -2 -1to Strata education elementary school teacher (PGSD). To expedite the qualification of primaryschool teachers in Indonesia is required college organizes undergraduate program (S-1) PGSDwith considerable capacity. To realize this the only alternative is the Open University as aninstitution of higher education distance that can accommodate a large number of studentswithout being limited by space and time. This is because the Open University uses distancelearning system with the concept of self-learning, so teachers who studied at the OpenUniversity does not have to leave his job as a teacher in the learning process.With the concept of self-owned learning expected of teachers graduated from S-1 PGSDOpen University is able to carry out his work in the learning process in school full independencein the face of all obstacles in school and in the community. The extent to which theindependence of teachers is implemented in the learning process? And how the performance ofprimary school teachers graduated from the Open University in the school ?. Researchers aretrying to find out "Independence and Elementary School Teacher Performance Tier One",Review of Social Reality Independence and Teacher Performance Open University Graduates inBojonegoro Region. The respondents of teachers drawn from schools in urban areas to thesuburbs in accordance with the criteria and character study. Independence (autonomy) andteacher performance is the focus of research. This research is using qualitative method in theanalysis of the data and produced a substantive theory development. Data taken byobservation, monitoring, and interviews in accordance with the method of qualitative research,the data on the independence of appropriate teacher competency responsibility, initiative,ability, satisfaction, and planning with indicators exist, and performance data of teachersregarding pedagogic , personality, social, and professional with accompanying indicators.The role of informants consisting of Bojonegoro district education offices, schoolprincipals, peers, school committees, and learners are very significant in providing datacompleteness and refinement of research results. While the implications for existing theories isto provide a basic understanding of independence, according to some experts and based onexisting research results, that independence is "independence means the state or the manner